Effects of Bacillus amyloliquefaciens Instead of Antibiotics on Growth Performance, Intestinal Health, and Intestinal Microbiota of Broilers - Wang, Baikui; Zhou, Yuanhao; Tang, Li; Zeng, Zihan; Gong, Li; Wu, Yanping; Li, Wei-Fen (Frontiers in Veterinary Science, 2021)
Abstract: The aim of this study was to evaluate the dietary effects of Bacillus amyloliquefaciens SC06 (SC06) instead of antibiotics on the growth performance, intestinal health and intestinal microbiota of broilers. A total of 360 30-day-old Lingnan yellow broilers were randomly allocated into two groups with 6 replicates per group (30 birds per replicate). The broilers were fed either a non-supplemented diet or a diet supplemented with 10^8 colony-forming units lyophilized SC06 per kilogram feed for 30 days. Results showed that SC06 supplementation had no effect on the growth performance compared with the control group. SC06 treatment significantly (P < 0.05) increased the total antioxidant capacity (T-AOC) and total superoxide dismutase (T-SOD) activity in liver, the activities of trypsin, α-amylase (AMS) and Na+K+-ATPase in the ileum, whereas (P < 0.05) decreased lipase, γ- glutamyl transpeptidase (GT) and maltase activities in the ileum. Meanwhile, SC06 treatment also improved the immune function indicated by the significant (P < 0.05) increased anti-inflammatory cytokine (IL-10) level and the decreased (P < 0.05) pro-inflammatory cytokine (IL-6 and TNF-α) levels in the ileum. Furthermore, we also found that SC06 enhanced the intestinal epithelial intercellular integrity (tight junction and adhesion belt) in the ileum. Microbial analysis showed that SC06 mainly increased the alpha diversity indices in in the jejunum, ileum and cecum. SC06 treatment also significantly (P < 0.05) increased the abundances of Bacteroidetes, Bacteroidales, Bacteroides, Fusobacteria, Clostridiaceae and Veillonellaceae in cecum, and simultaneously decreased the abundances of Planococcaceae in duodenum, Microbacteriaceae in jejunum and Lachnospiraceae, [Ruminococcus] and Ruminococcus in cecum. In conclusion, these results suggested that B. amyloliquefaciens instead of antibiotics showed a potential beneficial effect on the intestinal health of broilers.